2019
DOI: 10.3389/fphar.2019.00439
|View full text |Cite
|
Sign up to set email alerts
|

How to Prevent or Reduce Prescribing Errors: An Evidence Brief for Policy

Abstract: - Preventing prescribing errors is critical to improving patient safety. - We developed an evidence brief for policy to identify effective interventions to avoid or reduce prescribing errors. - Four options were raised: promoting educational actions on prudent prescribing directed to prescribers; incorporating computerized alert systems into clinical practice; implementing the use of tools for guiding medication prescribing; and, encouraging patient care by a multidiscipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…A policy brief summary analysing 40 systematic reviews, suggested actions dealing with prescribing error, including education for prescribers, incorporating computerised alerts, incorporating tools to guide prescribing, and encouraging multidisciplinary teams, including pharmacists, to care for patients [ 57 ]. This underlines that CPOE is only one intervention to reduce prescribing errors.…”
Section: Discussionmentioning
confidence: 99%
“…A policy brief summary analysing 40 systematic reviews, suggested actions dealing with prescribing error, including education for prescribers, incorporating computerised alerts, incorporating tools to guide prescribing, and encouraging multidisciplinary teams, including pharmacists, to care for patients [ 57 ]. This underlines that CPOE is only one intervention to reduce prescribing errors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple interventions were tested for efficacy in reducing medication errors and studies have documented that pharmacists play a major role in reducing these medication errors [14][15][16][17]. Ward-based clinical pharmacists reduce medication errors by providing real-time advice to physicians rather than recommending changes after prescribing has occurred [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Education and patient engagement in medication safety are key strategies in reducing medication errors ( Kim et al, 2018 ). Communication between practitioners is substantial, and it encourages all healthcare providers to be vigilant, detect and act on potential errors rather than rejecting them ( Araujo et al, 2019 ). Miscommunication of drug orders (illegible, ambiguous, incomplete, misunderstood order, and intimidation) is a common contributory factor to medication errors by healthcare providers.…”
Section: Discussionmentioning
confidence: 99%